Cellular Levels of Oxidative Stress Affect the Response of Cervical Cancer Cells to Chemotherapeutic Agents - Filippova, Maria (Biomed Res Int, 2014)
Treatment of advanced and relapsed cervical cancer is frequently ineffective, due in large part to chemoresistance. To examine the pathways responsible, we employed the cervical carcinoma-derived SiHa and CaSki cells as cellular models of resistance and sensitivity, respectively, to treatment with chemotherapeutic agents, doxorubicin, and cisplatin. We compared the proteomic profiles of SiHa and CaSki cells and identified pathways with the potential to contribute to the differential response. We then extended these findings by comparing the expression level of genes involved in reactive oxygen species (ROS) metabolism through the use of a RT-PCR array. The analyses demonstrated that the resistant SiHa cells expressed higher levels of antioxidant enzymes. Decreasing or increasing oxidative stress led to protection or sensitization, respectively, in both cell lines, supporting the idea that cellular levels of oxidative stress affect responsiveness to treatment. Interestingly, doxorubicin and cisplatin induced different profiles of ROS, and these differences appear to contribute to the sensitivity to treatment displayed by cervical cancer cells. Overall, our findings demonstrate that cervical cancer cells display variable profiles with respect to their redox-generating and -adaptive systems, and that these different profiles have the potential to contribute to their responses to treatments with chemotherapy.